ANALISA FAKTOR YANG BERHUBUNGAN DENGAN PENERAPAN INOVASI KELUARGA SEHAT DI WILAYAH KERJA PUSKESMAS - Astriana Butarbutar; Defry Stevani R (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2018)
Healthy family can be said as the condition and prosperous.circumstances. Both physically, socially to mentally that make it possible to become a whole family is consists of individuals who are led by a head of the family and live in an environment in order to live normally either economically or socially. This study aims to analyze the factors related to the application of healthy family innovation in the work area Public Health Center of Kalangan, ​​South Tapanuli. The type of this study is quantitative by using cross sectional approach. The population in this study is all residents in the working area of ​​Public Health Center of Kalangan that is Desa Aek Garut and Desa Sitio tio. The study started from January to May in 2018. The sample was 127 people with simple random sampling. Data analysis included univariate, bivariate to multivariate. The results showed that respondents who apply healthy family only 62.2% where as the age factor, knowledge, planning, monitoring, facilities / infrastructure and organizational staff related to applying healthy family innovation. It is recommended to the health office of Tapanuli Tengah to make supervision and direction for the community to implement healthy family program by increasing promotion and socialization of healthy families up to intergrated Service Post level and establish cooperation with community leaders.